Environmental problems in an industrial agglomeration: Strategies for solutions from natural science and socio-economic implications at the University of Cologne the special research area 419 - Friedrichs, Jürgen (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The article gives an overview of a large interdisciplinary research project at the University of Cologne directed at environmental problems in North-Rhine Westphalia, Germany. The project comprises 12 subprojects and the cooperation of 17 different academic disciplines. In the first part, the aims of the project are outlined and a brief outline of each project is given. To document the interdisciplinary approach, two projects are described in greater detail in the next two sections. The first assesses the impact of climate changes on ground water quality and analyzes whether the existing laws suffice to secure ground water quality. The second project studies the causes of a frequent nose disease, rhinosinusitis, in particular the relationships between indoor and outdoor pollution, and further examines this problem by specific cell cultures.